Temperate riverside forests without alder trees in the north-west of the Iberian Peninsula: ecology, phytosociological profile and interest for preservation policies - Rodríguez Guitián, Manuel Antonio (Lazaroa, 2011)
This paper describes three new riverside associations with no alder trees growing mainly along the middle and high altitude watercourses of the river basins located at the western end of the Cantabrian coast. Valeriano pyrenaicae-Fraxinetum excelsioris includes riverside mesoforests dominated by a combination of tree-like species (Fraxinus excelsior, Acer pseudoplatanus, Ulmus glabra, Quercus robur, Corylus avellana, Salix atrocinerea) which colonize the middle altitude watercourses of the rivers flowing into the Cantabrian Sea and the northern half of the Artabrian Gulf. Hyperico androsaemi-Coryletum avellanae comprises hazel and grey willow microforests associated with small tributaries and the high areas of the river basins within the thermo- and mesotemperate thermotypes of the territory. Finally, Violo palustris- Betuletum pubescentis is a tree association related to rivers flowing through the high mesotemperate and supratemperate areas of the northern ranges of Galicia and the Sierra de la Bobia in Asturias, continuing into the NW end of the Mino River basin. The above-mentioned forest types are all included in the 91E0* habitats of Appendix I of the Directive 92/43/EEC and are the habitat of a number of plant species of special interest for regional, Spanish and EU preservation policies.